Novel pathways of heart failure with preserved ejection fraction - Li, Shanpeng (2016)
INTRODUCTION: Diastolic heart failure (HF) i.e., HF with preserved ejection fraction (HFpEF) accounts for ~50% of all clinical HF presentations; but unlike systolic HF i.e., HF with reduced ejection fraction (HFrEF), there are no evidenced based therapies. Obesity is commonly associated with HFpEF. However, there exist a sub-group of obese patients that exhibit a higher survival rate to HFpEF as compared to average patients. Hypertension is the most important risk factor for HFpEF, with a prevalence of 60-89% reported by large controlled trials, epidemiological studies and HF registries. HFpEF morbidity and mortality rates are staggering: 50-60% 5 year mortality rate, 50% 6 month rehospitalization rate and severe clinical disability. However, there remains an incomplete mechanistic understanding about HFpEF.